Diagnostic Value of Fibrotic Indices in Egyptian Patients with Chronic Hepatitis and Hepatocellular Carcinoma - Hussien, Mohamed; Zahran, Faten; El-Emshaty, Hoda; Gouida, Mona Samy; Iqbal, Muhammad Naeem (PSM Biological Research, 2018)
Cirrhosis and hepatocellular carcinoma (HCC) end-stages of chronic liver diseases (CLD) are leading causes of morbidity and mortality worldwide. The main aetiologies of CLDs are chronic hepatitis C virus (HCV) infection. The aim of this work was to evaluate fibrotic indices APRI and FIB-4 in patients with chronic liver disease (CLD) with HCC, Cirrhosis, and healthy individuals. In the present study, we have investigated 30 Hepatocellular Carcinoma (HCC) patients, from Gastroenterology Center, Mansoura University, compared with 17 cirrhotic patients, and 25 normal healthy individuals as a control group. Laboratory liver fibrosis indices including FIB-4, APRI, and AST/ALT ratio were calculated in Egyptian patients with chronic hepatitis C virus. Results from this study were high APRI and FIB-4 in HCC patients compared with Cirrhosis and Control groups with significance difference (p<0.05). Based on our observation in this study APRI and FIB-4 which representing fibrotic indices have diagnostic value in the assessment of hepatocellular carcinoma.